2014
DOI: 10.1126/scisignal.2005602
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale functional analysis of the roles of phosphorylation in yeast metabolic pathways

Abstract: Protein phosphorylation is a widespread posttranslational modification that regulates almost all cellular functions. To investigate the large number of phosphorylation events with unknown functions, we monitored the concentrations of several hundred intracellular metabolites in Saccharomyces cerevisiae yeast strains with deletions of 118 kinases or phosphatases. Whereas most deletion strains had no detectable difference in growth compared to wild-type yeast, two-thirds of deletion strains had alterations in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 70 publications
2
34
0
Order By: Relevance
“…2014). Members of almost all arCOG categories were observed to be phosphorylated underpinning its fundamental role.…”
Section: Resultsmentioning
confidence: 99%
“…2014). Members of almost all arCOG categories were observed to be phosphorylated underpinning its fundamental role.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, metabolomics has proven to be a valuable tool in functional genomics to characterize unknown proteins (Ehebauer et al, 2015). As enzyme inactivation leads to upstream accumulation of metabolites (Fendt et al, 2010), whereas protein activity modulation through post-translational modification or protein interaction also impacts metabolism (Oliveira et al, 2012;Schulz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lysine metabolism was found to be exclusively enriched ( p -value 0.006) in Lys20 OUT when growing on glucose/proline. While lysine biosynthesis is known to be subject to transcriptional and allosteric control, it was recently shown that Lys20 activity is also regulated by phosphorylation [26, 35]. Metabolite responses in Lys20 OUT were observed only during growth on the poor nitrogen source proline and significant ( p -value < 10 −3 , |log2 fold change| > 0.3785) changes were restricted to the final pathway product lysine and its precursor saccharopine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A notable exception is mass spectrometry-based metabolomics. In particular, it offers the potential to identify small differences in metabolite profiles well before a change of the phenotype is observed [25, 26]. Since many of the phosphoproteins listed in phosphosite databases are part of the metabolic network, metabolomics is a promising approach for probing their functionality.…”
Section: Introductionmentioning
confidence: 99%